2019
DOI: 10.1002/ange.201813052
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Cobalt‐Based Electrocatalysts with Facile Incorporation of Dopants for the Oxygen Evolution Reaction

Abstract: In situ formation of electroactive cobalt species for the oxygen evolution reaction is simply achieved by applying an anodic bias to ac ommercially available cobalt precursor and Nafion binder mixture coated on aglassy carbon electrode. This preparation does not require energy-intensive materials preparation steps or noble metals,y et al ow overpotential of 322 mV at 10.2 mA cm À2 and ah igh current density of more than 300 mA cm À2 at 1.7 V NHE were obtained in 1m KOH. An operando electrochemical Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…As displayed in Fig. 1b , a number of bright spots are clearly observed, in which Fe/Mn atomic pairs are randomly distributed on the surface of N-doped carbon as highlighted by red cycles, attributed to heavy Fe, Mn than light N, C atoms 35 . In order to make it clearer whether Mn–N 4 is adjacent to Fe–N 4 , the atomic-resolution HAADF-STEM of Fe–N–C and Mn–N–C catalysts have been additionally carried out.…”
Section: Resultsmentioning
confidence: 95%
“…As displayed in Fig. 1b , a number of bright spots are clearly observed, in which Fe/Mn atomic pairs are randomly distributed on the surface of N-doped carbon as highlighted by red cycles, attributed to heavy Fe, Mn than light N, C atoms 35 . In order to make it clearer whether Mn–N 4 is adjacent to Fe–N 4 , the atomic-resolution HAADF-STEM of Fe–N–C and Mn–N–C catalysts have been additionally carried out.…”
Section: Resultsmentioning
confidence: 95%
“…), but it is still unclear that the promoting effect of OER is from the complex material composition or from the in situ generated thin layers of hydroxide/ oxyhydroxide. Thus, developing an universal and facile approach to obtain the catalysts with highly efficient and well‐defined structure is highly desirable, which not only can satisfy the industrial demands mentioned above, but also can well explore the active sites and mechanism of catalysts …”
Section: Introductionmentioning
confidence: 99%
“…The sites are a result of the formation of mixed iron-cobalt (oxy)hydroxides. As studied by some of us, the rigid structure of Co 3 O 4 obtained by nanocasting was less susceptible to iron contamination 43,53 than the less crystalline material studied by Smith et al 5 Cyclic voltammograms recorded after SI-SECM experiments showed that the redox peak I a at ~1.25 V is vanishing (Figure S8). This could be explained by an anodic shift due to electronic effects by the substitution of Co II by Fe III or by an irreversible oxidation of some Co II sites to Co III during SI-SECM.…”
Section: Time-dependent Si-secm Experimentsmentioning
confidence: 88%
“…The identification of Co IV species is very challenging even with spectroscopic techniques. 5,14,[42][43][44] In contrast to Eq. (1)-( 3), the different redox peaks in the voltammogram have also been described as transition of solely Co II to Co III , where the segmentation results from different structural motifs.…”
Section: Cyclic Voltammetrymentioning
confidence: 92%
See 1 more Smart Citation